2021
DOI: 10.1186/s12889-021-12054-3
|View full text |Cite
|
Sign up to set email alerts
|

Over-the-counter analgesics use is associated with pain and psychological distress among adolescents: a mixed effects approach in cross-sectional survey data from Norway

Abstract: Background Over-the-counter analgesics (OTCA) such as Paracetamol and Ibuprofen are frequently used by adolescents, and the route of administration and access at home allows unsupervised use. Psychological distress and pain occur simultaneously and are more common among females than among males. There is a dynamic interplay between on-label pain indications and psychological distress, and frequent OTCA use or misuse can exacerbate symptoms. No studies have to date provided an overview of freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 61 publications
4
17
1
2
Order By: Relevance
“…Close to 10% of the adolescents in our study reported using OTCA for headache weekly or daily and 3.5% reported use for musculoskeletal pain weekly or daily. These findings comply with previous studies showing that a substantial subgroup of adolescents use OTCA frequently 2 4 10. Such weekly use will generally represent overuse and may have negative health effects 11 43…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Close to 10% of the adolescents in our study reported using OTCA for headache weekly or daily and 3.5% reported use for musculoskeletal pain weekly or daily. These findings comply with previous studies showing that a substantial subgroup of adolescents use OTCA frequently 2 4 10. Such weekly use will generally represent overuse and may have negative health effects 11 43…”
Section: Discussionsupporting
confidence: 91%
“… 2 4 56 In terms of depression and anxiety, these conditions have been found to be associated with using OTCA more frequently also after adjusting for pain. 4 There is also an overlap between social factors related to trauma and to chronic pain, including a less favourable family environment and poorer peer relational skills. 49 Thus, it is plausible that physiological and psychological trauma reactions and related social problems may contribute to more frequent use of OTCA among trauma-exposed adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, as cancer survivors comprise about 0.5% of the child population and most survivors do not require long-term pain management, this cannot fully explain the overall increase in prescription analgesics use [ 55 ]. This leaves the possibility that conditions which do not indicate use of pain medication that seem to be increasing in younger age groups, such as chronic pain or psychological distress, may have contributed to higher use of prescription analgesics [ 24 , 27 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sales of paracetamol are second on the OTC list. A Norwegian study showed that 30% of female and 13% of male adolescents aged 13-19 use OTC analgesics weekly (Jonassen et al, 2021). Daily use of paracetamol, even in small doses, can give rebound headaches (Fischer & Jan, 2021).…”
Section: Risks Associated With the Top Selling Otcsmentioning
confidence: 99%